1993
DOI: 10.1213/00000539-199302000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance for Intraoperative Transesophageal Echocardiography Monitoring

Abstract: We evaluated our experience with 846 consecutive transesophageal echocardiography (TEE) intraoperative monitoring procedures performed between November 1989 and July 1991. TEE frequency was 36 +/- 11 per month (range 16-55) and represented 69.8% of cardiac valve surgery cases, 40.2% of coronary artery bypass graft cases, and 2.2% of total operative caseload. Major patient complications consisted of transient vocal cord paresis and ingestion of glutaraldehyde-disinfectant solution. Minor complications consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Increasing availability of TOE may also allow decreased use of pulmonary catheterization with its associated complications [23][24][25] . Additionally, in the near future, application of myocardial contrast echocardiography may further increase the utility of intraoperative TOE by allowing direct confirmation of coronary revascularization and cardioplegia delivery 26 .…”
Section: Intraoperative Echocardiographymentioning
confidence: 99%
“…Increasing availability of TOE may also allow decreased use of pulmonary catheterization with its associated complications [23][24][25] . Additionally, in the near future, application of myocardial contrast echocardiography may further increase the utility of intraoperative TOE by allowing direct confirmation of coronary revascularization and cardioplegia delivery 26 .…”
Section: Intraoperative Echocardiographymentioning
confidence: 99%
“…An updated report by the American Society of Anesthesiologists and the Society of Cardiovascular Anesthesiologists Task Force on Transesophageal Echocardiography 2010 ). Studies have reported that TEE significantly improved the intraoperative management of patients undergoing OLT (Suriani et al 1996 ; Rafferty et al 1993 ). One study, although not conducted during intraoperative OLT procedures, showed that “TEE without transgastric views can be performed without serious complications in patients with grade I or II esophageal varices who have not experienced recent variceal hemorrhages”(Spier et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Además, no todos los cambios de la motilidad de la pared ventricular corresponden a isquemia: bloqueos en la conducción y el uso de inótropos pueden producirlos. Otra restricción de tipo técnico se plantea en cuanto a la imposibilidad de mantenerlo en el postoperatorio, por ser muy mal tolerado por el paciente [31][32][33] .…”
Section: E S T I G a C I ó Nunclassified